REIWA Curtin Buy-Rent Index - Ho, J-Han; Kazalac, L.; Bhimjiani, R.; Kanbi, D. (Real Estate Institute of Western Australia (REIWA), 2017)
The REIWA Curtin Buy-Rent Index is a tool to assess whether it is a better time to buy or rent based on past and current trends in the economic climate. The Buy-Rent Index does not represent the performance of an individual property, but instead looks at aggregate median house prices.